Carbon quantum dots from glucose oxidation as a highly competent anode material for lithium and sodium-ion batteries. (20th February 2019) - Javed, Mohsin; Saqib, Ahmad Nauman Shah; Ata-ur-Rehman,; Ali, Basit; Faizan, Muhammad; Anang, Daniel Adjah; Iqbal, Zafar; Abbas, Syed Mustansar
Abstract: Carbon quantum dots derived from the chemical oxidation of D-(+)-glucose have been efficiently synthesized in good yield using a simple and economically viable approach. Carbon quantum dots possess a quasi-spherical structure with facile storage and transport channels for lithium and sodium-ions. When applied as an anode for the lithium-ion battery, the as-prepared quantum dots demonstrate a superior and stable cycling performance after 500 cycles (864.9 mAh g −1 at 0.5 C) with capacity retention of 91.6%, and a good rate performance (340.2 mAh g −1 at 20 C). As a sodium-ion battery anode, the quantum dots present a specific capacity of 323.9 mAh g −1 at 0.5 C and capacity retention of 72.4% after 500 charge/discharge cycles, indicating an excellent cycling stability. A relatively moderate rate performance of 123.6 mAh g −1 is achieved at the 20 C rate. This study demonstrates the use of individual quantum dots as a potential electrode material for lithium-ion, and sodium-ion battery applications, and it will definitely result in the fabrication of new composite materials in the energy-storage field. The extreme downsizing to the quantum regime has led to the achievement of utmost properties that have been prescribed to the quantum effects, efficient ion diffusion, and the charge transfer. Graphical abstract: Image 1 Highlights: CQDs are derived from D-(+)-glucose via a simple and economically viable approach. CQDs as electrode with significant electrochemical performance in Li- and SIBs. Superior and stable cycling presenting 864.9 mAh g −1 at 0.5 C as LIB anode. Specific capacity of 323.9 mAh g −1 at 0.5 C as SIB anode with good rate performance.